Bihari Muharram processions in Dhaka city: religious performance as a means of territorialising urban public space by a disenfranchised ethnic minority. Issue 2 (26th May 2020) - Fattah, Kazi Nazrul
Abstract : The Biharis in Bangladesh are a heavily persecuted ethnic minority confined to slum like camps for nearly five decades. Using data from ethnographic research carried out in a Bihari camp and its surrounding areas in Dhaka city, this visual essay examines the ways in which the Biharis use religious processions to claim visibility, assert community identity and territorialise urban public space in a city that systematically denies them access to citizen rights.